2012
DOI: 10.3109/02699052.2012.667591
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical study of routine repeat computed tomography (CT) after traumatic brain injury (TBI)

Abstract: The routine-repeat CT group fared better than did the non-routine-repeat CT group. Routinely repeated CTs were minimally effective among those with mild TBI, whereas this procedure demonstrated a significant effect on patients with moderate and severe TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…It is also reported that a series of CT scans in non-operative EDH patients should be obtained within 6 to 8 hours after the initial injury for better outcomes with prompt decision of treatment 20). Moreover, Ding et al3) reported that the non-surgical patients with routine repeat CT scans have a better outcome than those with non-routine repeat CT. However, the same authors also mentioned that routine follow-up CT scans 48 hours after trauma may not also be required 316)…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that a series of CT scans in non-operative EDH patients should be obtained within 6 to 8 hours after the initial injury for better outcomes with prompt decision of treatment 20). Moreover, Ding et al3) reported that the non-surgical patients with routine repeat CT scans have a better outcome than those with non-routine repeat CT. However, the same authors also mentioned that routine follow-up CT scans 48 hours after trauma may not also be required 316)…”
Section: Discussionmentioning
confidence: 99%
“…As identifying the actual injury time cannot be verified in many trauma cases, we supposed that the time elapsed from the initial CT was more practical. The Ding et al 13 RCT reported that 80% of patients (56 out of 70) complicated with progression of TBI did so within 24h and the remaining 20% were delayed 24-48 h. Epidural hematoma, non-operatively treated in accordance with the guidelines, in a prospective non-controlled study, 11 have shown EDHP in 10% of patients, occurring within 12h in 6 out of 70 patients and 24 h in 1 patient. However, they excluded another patient who developed EDHP after four days.…”
Section: Time Interval For Edhpmentioning
confidence: 98%
“…9,11 Epidural hematoma progression represented 7.9% of all cases of TBI progression in a randomized controlled trial. 13 The risk factors of such progression are still not very obvious and the literature has seldom addressed this issue with specific attention and mostly in studies prior to the publication of the BTF surgical guidelines. We carried out this study to identify which patients, among those candidates with EDH, suitable for an initial non-operative treatment, are at greater risk of EDHP, and to determine when they become surgical candidates.…”
mentioning
confidence: 99%
“…Cranial CT is the most frequently used imaging modality during the pre-and post-operative periods in EDH. The followup is made with frequent cranial CTs in unoperated patients [8,9]. In our study, the mean number of CT scans for the follow-up of EDH was 3.7.…”
Section: Discussionmentioning
confidence: 64%